Prediction on water quality of point source pollution for Lunchoo River, Johor - Shahperi, Rafidah (2010)
The growth in population and expansion in urbanization, industrialization and irrigated agriculture are imposing growing demands and pressure on water resources, besides contributing to raise water pollution. As a case in point, Lunchoo River was initiated to be the contribution of water quality deterioration with regional consequences on the aquatic ecosystem and on the health of the downstream sub-basin’s user group. Thus, a balance strike between those developments and a good quality of life that has to be considered in the complex relationship between water quality and quantity on one hand and human health and well being on the other. In this study, a limitation on point sources pollutant and low flow condition are accounted for industrialization sectors within Lunchoo River catchment boundary. Approached of Mass Balance concepts are put into practice in order to analyze the situation. However, an understanding of the existing river characteristic and waste stream characteristic is deemed necessary to determine the background level of pollutant. Output generated from this study is important because it is a vital key toward an optimal management of its resources. Then, comparison between the current standard limit or guideline and the result achieved will determine the stage of pollutant. Therefore, the outcome of this study will determine the water quality of Lunchoo River and it is one of the initiative to ensure the water quality and environment been properly manage at Lunchoo River, as it is the most important sources of raw water to satisfy the clean water supply demand for the entire Johore State and also Singapore.